(untitled) (Research, Society and Development, 2021)
Objective: To identify the association between cumulative fluid balance in the first 72 hours of ICU stay and outcomes. Methodology: retrospective observational cohort with data analysis of adult patients hospitalized in an ICU of a tertiary teaching hospital. Results: a total of 86 patients who remained in the ICU for more than 72 hours were evaluated. The fluid balance in the first 72 hours was higher in the subgroup of patients who died in the ICU (5210.3 ± 2787.7 vs. 3017.4 ± 2847.2 mL, p = 0.004). The fluid balance in the first 72 hours was an independent factor directly associated with death in the ICU (OR: 1,000; p = 0.009). The area under the ROC curve was 0.7119 (95% CI: 0.58-0.84, p = 0.005). The optimal cutoff point for the fluid balance in the first 72 hours as a predictor of death in the ICU was + 3.900mL and the relative risk of death among those who presented a fluid balance higher than this value was 1.702 (95% CI: 1, 15-2.53, p = 0.009). Conclusion: an association was identified between the cumulative value in the fluid balance in the first 72 hours of ICU stay and the highest risk of death, which is an independent factor of the patient’s severity at admission.